Sustainability and Cities : Concept and Assessment. (World Scientific, 2005)
For the past 20 years, the Third World Academy of Sciences (TWAS) has been at the forefront of efforts to promote science and science-based developments in the developing world. This history of TWAS, the first of its kind, seeks to examine the forces that led to the creation of TWAS and that have sustained its growth and development ever since. This is a history of an organization that has made a difference in the advancement of science in the developing world and one that has been operated largely by and for scientists from the South. It provides a unique perspective on the challenges and opportunities that have driven science in the South over the past two decades and offers a window on the progress that has been made and the enormous amount of work that still needs to be done.